The effect of Toll-like receptor agonists on the immunogenicity of MVA-SARS-2-S vaccine after intranasal administration in mice - Do, Kim Thi Hoang; Willenzon, Stefanie; Ristenpart, Jasmin; Janssen, Anika; Volz, Asisa; Sutter, Gerd; Förster, Reinhold; Bošnjak, Berislav (Frontiers in Cellular and Infection Microbiology, 2023)
Background and aims: Modified Vaccinia virus Ankara (MVA) represents a promising vaccine vector for respiratory administration to induce protective lung immunity including tertiary lymphoid structure, the bronchus-associated lymphoid tissue (BALT). However, MVA expressing the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Spike protein (MVA-SARS-2-S) required prime-boost administration to induce high titers of anti-Spike antibodies in serum and bronchoalveolar lavage (BAL). As the addition of adjuvants enables efficient tailoring of the immune responses even to live vaccines, we tested whether Toll-like receptor (TLR)-agonists affect immune responses induced by a single dose of intranasally applied MVA-SARS-2-S.We intranasally immunized C57BL/6 mice with MVA-SARS-2-S vaccine in the presence of either TLR3 agonist polyinosinic polycytidylic acid [poly(I:C)], TLR4 agonist bacterial lipopolysaccharide (LPS) from Escherichia coli, or TLR9 agonist CpG oligodeoxynucleotide (CpG ODN) 1826. At different time-points after immunization, we analyzed induced immune responses using flow cytometry, immunofluorescent microscopy, and ELISA.Results: TLR agonists had profound effects on MVA-SARS-2-S-induced immune responses. At day 1 post intranasal application, the TLR4 agonist significantly affected MVA-induced activation of dendritic cells (DCs) within the draining bronchial lymph nodes, increasing the ratio of CD11b + CD86 + to CD103 + CD86 + DCs. Nevertheless, the number of Spike-specific CD8 + T cells within the lungs at day 12 after vaccination was increased in mice that received MVA-SARS-2-S co-administered with TLR3 but not TLR4 agonists. TLR9 agonist did neither significantly affect MVA-induced DC activation nor the induction of Spike-specific CD8 + T cells but reduced both number and size of bronchus-associated lymphoid tissue. Surprisingly, the addition of all TLR agonists failed to boost the levels of Spike-specific antibodies in serum and bronchoalveolar lavage.Our study indicates a potential role of TLR-agonists as a tool to modulate immune responses to live vector vaccines. Particularly TLR3 agonists hold a promise to potentiate MVAinduced cellular immune responses. On the other hand, additional research is necessary to identify optimal combinations of agonists that could enhance MVA-induced humoral responses.